2017
DOI: 10.1016/j.clinbiomech.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The recovery response to a novel unannounced laboratory-induced slip: The “first trial effect” in older adults

Abstract: Background After a single slip, older adults rapidly make adaptive changes to avoid or eliminate further backward loss of balance or a fall. This rapid adaptation has been termed the “single trial effect”. The purpose of this study was to explore the relationship between the motor errors subjects experienced upon a novel slip and the selection and execution of corrective response by which they modified their ongoing gait pattern and turned it into a protective step. Methods A forward slip was induced in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…This study only used one trial for analyzing the novel slip response compared to three trials each for the early and late phase. This was done as it is widely known that a single slip trial exposure is sufficient to induce adaptive changes – known as the first-trial effect 23 , 33 . Thus, using an average of the first three trials would contaminate the true novel slip response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study only used one trial for analyzing the novel slip response compared to three trials each for the early and late phase. This was done as it is widely known that a single slip trial exposure is sufficient to induce adaptive changes – known as the first-trial effect 23 , 33 . Thus, using an average of the first three trials would contaminate the true novel slip response.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely known that a single slip trial exposure is sufficient to induce changes in reactive balance, which is known as the first-trial effect 23 , 33 . After a single slip exposure, individuals show significant improvements in stability and a reduction in the slip distance on the second slip, even though a majority (> 80%) still lose their balance 11 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, multicomponent PEPs provide an instantaneous snapshot of cortical changes related to reactive balance tasks; however, a majority of studies have used average trial analysis to quantify them. Previous neurophysiological studies have indicated that perturbation-induced motor adaptation can occur in as little as a single trial in healthy young and older adults [ 104 , 105 , 106 ]. Hence, future studies should test the feasibility and robustness of using single-trial PEP analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, friction is likely to stay linear as we previously tested static coefficient of friction of the WASP under a range of simulated body weights and it did not change ( 7 ). Learning effects may arise after exposure to the first slip despite being exposed to different types of slip onset phases during stance, hence this could be a limiting factor, especially since literature reported biomechanical and motor adaptation after a single exposure to sagittal induced ( 54 , 55 ) and unconstrained induced ( 56 ) in-lab slips. The previously mentioned studies did not report the exact resting period between each slip trial, and despite the resting period (5-min) was controlled in this study, it is uncertain if such resting period is sufficient to exclude proactive adaptation.…”
Section: Discussionmentioning
confidence: 99%